Relationship Level Of Knowledge Of Mother With Giving Immunization In Infants 0-12 Months At The Mompang Health Center Jae, Panyabungan Utara Kabupaten Mandailing Natal In 2022 - Emelia Apriani Tampubolon; Rizky Andriani Bakara (Jurnal EduHealth, 2023)
Immunization is an effort to increase individual immunity to avoid certain diseases. Immunizations that must be given to babies are Hepatitis B, polio, BCG, DPT, measles. Complete basic immunization coverage in Indonesia in 2019 was 71.98%. This research is an analytic survey with a cross-sectional approach. Sampling in this study using a total sampling technique that is as many as 35 people. The research instrument uses primary data (questionnaire) which consists of 20 questions. Data processing techniques started from editing, coding and tabulating, then tested with the Chi-Squer test. The results of this study indicate that immunization was administered in 35 cases, the majority of whom had moderate knowledge of 14 people (40.0%) and the minority of knowledge lacking 9 people (25.7%). The results of the Chi-Square test obtained p-value = 0.001 <0.05, so Ha was accepted and Ho was rejected, which means that there is a relationship between the level of knowledge of mothers and the administration of immunizations for babies 0-12 months in the working area of ​​the Mompang Jae Health Center, Panyabungan Utara Kabupaten Mandailing Natal in 2022